Religious Authority and Political Dynamics: The Influence of Fatwa Issuance by Religious Institutions on Political Discourses in Indonesia - K.A. Bukhori; Kun Budianto; Erniwati Erniwati; Moh. Faizal (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study explores the role of religious institutions through fatwas in the formation of public policy in Indonesia, particularly major institutions such as the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah. The main objective is to understand how fatwas are produced by religious organizations and how they impact the political process and government policy. The research problem stems from the phenomenon that fatwas, although they do not have formal legal force, are often used as moral references by the community and are even considered by the government in formulating public policy. The research approach uses qualitative field studies: interviews with fatwa figures, analysis of fatwa documents, and observation of the interaction between religious institutions and public officials in several regions. The findings show that fatwas serve as moral and social legitimacy as well as non-formal influence on the formulation of public policy. Although not legally binding, the influence of fatwas on policy guidance is quite significant, especially on moral and social issues, as well as the creation of a space for dialogue between the state and society. The implications of the research results show the importance of understanding the role of fatwas not only as religious products but also as social political instruments in the architecture of public policy. Abstrak Penelitian ini mengeksplorasi peran lembaga keagamaan melalui fatwa dalam pembentukan kebijakan publik di Indonesia, khususnya lembaga-lembaga utama seperti Majelis Ulama Indonesia (MUI), Nahdlatul Ulama (NU), dan Muhammadiyah. Tujuan utama adalah memahami bagaimana fatwa diproduksi oleh organisasi keagamaan dan bagaimana dampaknya terhadap proses politis dan kebijakan pemerintah. Masalah penelitian berangkat dari fenomena bahwa fatwa, meskipun tidak memiliki kekuatan hukum formal, sering dijadikan rujukan moral oleh masyarakat dan bahkan dipertimbangkan pemerintah dalam merumuskan kebijakan publik. Pendekatan penelitian menggunakan studi lapangan kualitatif: wawancara dengan tokoh fatwa, analisis dokumen fatwa, dan observasi interaksi lembaga keagamaan dengan pejabat publik di beberapa daerah. Temuan menunjukkan bahwa fatwa berfungsi sebagai legitimasi moral dan sosial sekaligus pengaruh nonformal terhadap perumusan kebijakan publik. Meskipun tidak bersifat mengikat secara hukum, pengaruh fatwa terhadap panduan kebijakan cukup signifikan, terutama dalam isu moral dan sosial, serta penciptaan ruang dialog antara negara dan masyarakat. Implikasi hasil penelitian menunjukkan pentingnya memahami peran fatwa bukan hanya sebagai produk keagamaan, tetapi juga sebagai instrumen politik sosial dalam arsitektur kebijakan publik.